La glorieta miniatura: generic manifesto of the micro-fiction (XXI Century. Spanish Literature and Culture, 2017)
Jose Mª Merino is not only one of the most established contemporary authors of the Spanish micro fiction, but also, as a creator, he has contributed new keys to the study of this type of texts from several perspectives; while in La trama oculta: cuentos de los dos lados con una silva mínima Merino brings together several essays in which dissects the essential characteristics of the short fiction, we also find the metamicrorrelatos collected in La glorieta miniatura, through which the the writer constructs a meticulous poetics about the genre, defining many of its foundational features. La glorieta de los fugitivos is the book that brings together almost all of its texts dedicated to micro-fiction; This volume consists of three parts: the first composed by Días imaginarios, Cuentos del libro de la noche e Inéditos y dispersos; the second, the La glorieta miniatura (veinticinco pasos)  and, finally, an appendix with Diez cuentines congresistas. It is precisely these last two sections that interest us: the first to constitute in itself a theoretical manifesto of the micro-story; and the second to present, alluding to the specialists to whom they are addressed, the controversies that this genre is capable of awakening
Keywords: José María Merino